Air pollution prevention and control : bioreactors and bioenergy - Kennes, C.; Veiga, M. C. (Hoboken : John Wiley & Sons Inc., 2013)
Air Pollution Prevention and Control : Bioreactors and Bioenergy is the first reference work to give a broad overview of bioprocesses for the mitigation of air pollution. Primarily intended for researchers and students in environmental engineering, biotechnology and applied microbiology, the book will also be of interest to industrial and governmental researchers.--COVER.
pt. 1. Fundamentals and microbiological aspects -- Introduction to air pollution -- biodegradation and bioconversion of volatile pollutants -- Identification and characterization of microbial communities in bioreactors -- pt. 2. Bioreactors for air pollution control -- Biofilters -- Biotrickling filters -- Bioscrubbers -- Membrane bioreactors -- Two-phase partitioning bioreactors -- Rotating biological contactors -- Innovative bioreactors and two-stage systems -- pt. 3. Bioprocesses for specific applications -- Bioprocesses for the removal of volatile sulfur compounds from gas streams -- Bioprocesses for the removal of nitrogen oxides -- Biogas upgrading -- pt. IV. Environmentally-friendly bioenergy -- Biogas -- Biohydrogen -- Catalytic biodiesel production -- Microalgal biodiesel -- Bioethanol -- pt. V. Case studies -- Biotrickling filtration of waste gases from the viscose industry -- Biotrickling filters for removal of volatile organic compounds from air in the coating sector -- Industrial bioscrubbers for the food and waste industries -- Desulfurization of biogas in biotrickling filters -- Full-scale biogas upgrading.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Air -- Pollution; Air -- Purification; Bioreactors; Biomass energy; TECHNOLOGY & ENGINEERING -- Environmental -- Pollution Control; Air -- Pollution; Air -- Purification; Biomass energy; Bioreactors; Electronic books